Оptimization of parameters of signals of the antenna unit of the GPR "Odyag" - Батраков, Д. О.; Почанин, Г. П.; Холод, П. В.; Рубан, В. П.; Орленко, А. А.; Кундиус, А. С. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
By use of designed measurement units we defined impulse of the GPR "Odyag" "butterfly" dipole antennas form. Provided numerical experiments for modeling work GPR antenna units allow us to determine the real shape of the primary pulse signals used for probing and set the features of the interaction of receiving antennas in the implementation of the principle of compensation frequency-independent direct path signal. Analysis of the shape of the synthesized signal by the computer software allowed us to justify the optimal distance between the receiving antennas in the present case. The results are intended to provide increasing the spatial resolution of ground penetrating radar and reliability of pulsed signal processing results